Antimicrobial Strategies for Bacterial Contaminants during Ethanol Production from Cellulosic Crop Residues - Udhayaraja, P (International Journal of Pharmaceutical & Biological Archive, 2012)
Antimicrobial Strategies for Bacterial Contaminants during Ethanol Production from Cellulosic Crop Residues